The Effect of Diabetes on Health-Related Quality of Life in Emirati Patients - Zainab Al-Abadla; Targ Elgzyri; Mayada Moussa (Dubai Diabetes and Endocrinology Journal)
Background: Diabetes mellitus (DM) is known to negatively affect quality of life (QoL), yet very few studies have been done on QoL of patients with diabetes in the United Arab Emirates population. Objectives: The aim of this study was to assess the impact of DM on health-related QoL (HRQoL) of patients with diabetes of Emirati nationality. Methods: Two hundred and forty Emirati patients with diabetes, treated at the Dubai Diabetes Center, were randomly selected and interviewed using the Short Form-36 questionnaire to assess HRQoL domains. Appropriate statistical measures were performed to associate HRQoL domains with diabetes-related factors. Results: HRQoL satisfaction scores for physical and mental health domains were very high for the majority of participants. Male participants ranked significantly higher median scores in all HRQoL domains than females (77.36 vs. 65.28, p = 0.004). There was a significant (p < 0.001) negative correlation between diabetes duration and the total averaged score for all sub-domains, and significant (p < 0.001) negative correlations between glycated hemoglobin percentage (HBA1c%) and all sub-domains of HRQoL. Patients without complications had significantly better scores in all HRQoL sub-domains than patients suffering from any complications. Median total HRQoL score for those with neuropathy compared to those without neuropathy was 63.9 versus 82.6 (p < 0.001), for nephropathy was 43.6 versus 72.5 (p < 0.001), for retinopathy 50.7 versus 76.0 (p < 0.001), for ischemic heart disease 54.1 versus 77.3 (p < 0.001), and for cerebrovascular disease 36.7 versus 72.4 (p < 0.001). Multiple regression showed 3 significant predictors for the total averaged score from all HRQoL sub-domains; these were age (p = 0.007), HbA1c% (p < 0.001), and the number of complications related to DM (p = 0.001). Conclusion: HRQoL in Emirati patients with diabetes was significantly associated with the presence of diabetes-related complications, glycemic control, and age of the patient. The assessment of QoL in patients with diabetes can be a valuable measure for the healthcare providers to assess patient’s well-being.